Aktuelles zur kutanen Neurobiologie von Pruritus - Raap, Ulrike; Schmelz, Martin (Der Hautarzt, 2016)
The pathogenesis of chronic and acute pruritus is not yet completely understood. Interactions of neurons with resident and nonresident skin cells seem to play an important role in the regulation of pruritus. Neuronal cells which express specific receptors and are capable of releasing neuromediators play an active role in this interaction. Furthermore, released neuromediators can activate immune cells including mast cells and eosinophils, which are increased in the inflammatory infiltrate of many pruritic skin diseases. Mast cells and eosinophils express receptors for neuromediators themselves. In addition, they can release neurotrophins including nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) and cytokines including interleukin (IL)-31 which correlate with disease activity in patients with inflammatory skin diseases including atopic dermatitis and induce neuronal outgrowth. In part, a correlation of these mediators has also been described with pruritus. Although the interplay between transient and resident cells in the skin with peripheral nerves, mast cells, and eosinophils plays an important role in the mutual activation, the neurobiological mechanisms that lead to pruritus are not completely clear yet.
Gesehen am 13.08.2019